2018
DOI: 10.14687/jhs.v15i2.4784
|View full text |Cite
|
Sign up to set email alerts
|

How does gender impact the relationship between reading fluency and reading comprehension?<p>Akıcı okuma ve okuduğunu anlama arasındaki ilişkilerde cinsiyet nasıl bir rol oynamaktadır?

Abstract: This research aimed to explore how gender impacts the relationship between reading fluency and reading comprehension. The research sample consists of a total of 100 seventh graders. In order to assess the students' reading comprehension and reading fluency levels, an expository and a narrative text were used. For the implementations, each student was asked to read orally the expository text and answered the comprehension questions related to texts. The same procedure was used for the narrative text reading. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Çetin (2017) conducted a study on 387 elementary school fourth grade students in Muğla and found that the female students' reading comprehension scores are higher than those of the male students. Kaya and Yıldırım (2018) compared fluent reading and reading comprehension on the basis of gender and found that they do not vary significantly depending on gender. These differences between the research findings may have resulted from the differences of samplings and data collection tools.…”
Section: Resultsmentioning
confidence: 99%
“…Çetin (2017) conducted a study on 387 elementary school fourth grade students in Muğla and found that the female students' reading comprehension scores are higher than those of the male students. Kaya and Yıldırım (2018) compared fluent reading and reading comprehension on the basis of gender and found that they do not vary significantly depending on gender. These differences between the research findings may have resulted from the differences of samplings and data collection tools.…”
Section: Resultsmentioning
confidence: 99%
“…The second method is to make use of the material that is accessible in a manner that is engaging to the audience (Büyükkarada, 2017;Haris, 1990). The more complex explanation about the aspect in improving student's motivation in reading is given by Kaya (2018) in which he explains that the practice of using interesting texts to build students' motivation in reading refers to the teaching from the sample of books, material, and technology that are relevant to the learning and knowledge goal. It implies that the teacher should use appropriate materials and media to encourage students to read so that they develop an interest in reading.…”
Section: Reading Motivationmentioning
confidence: 99%